MANAJEMEN MEDIA RELATIONS DALAM MENINGKATKAN CITRA POSITIF DAN REPUTASI PERUSAHAAN DI ERA ARTIFICIAL INTELLIGENCE - Riza Nur Rizqiyah; Rachmat Kriyantono; Anang Sujoko (Universitas Lambung Mangkurat, 2021)
In the current disruptive era, the need for information access is becoming easier and is developing practically. One of the developments in technology and digitalization that has made progress in infrastructure and innovation in people's lives is the presence of artificial intelligence (AI), which provides convenience in helping jobs supported by big data. As a continuation of Public Relations activities in the current era, in building relations between organizations or companies and the public, media relations is one of the roles of PR in relation management. This study aims to discuss media relations management in enhancing the company's positive image on elements of public relations transformation in the 4.0 era. By using the literacy study method, this research is presented in a descriptive qualitative way to analyze data relating to the company's media relations management by mobilization and digitalization. The results found in this study are the role of AI is very helpful and easy in public relations work, especially in media relations activities. For companies, the presence of AI helps in managing the media used by the company as a form of disseminating information through social media owned by the company itself (owned media) which is done in real time. So that in the management of information through social media requires deception of content and media monitoring aimed at evaluating public relations in media relations activities that are able to enhance the company's positive image.